Effects of Recovery Techniques in Reducing Fatigue Levels of Badminton Athletes in Sumenep District - Ainur Rasyid; Nugroho Agung Supriyanto; Oce Wiriawan; Andi Fepriyanto; Dian Helaprhara (Universitas Pendidikan Indonesia, 2024)
This study provides new insights into the differences of lactate clearance between the active recovery and the passive recovery using CWI techniques. The method used in this research was the pure experimental research (actual experimental design) with a randomized control group pretest-posttest design. The samples were randomly selected and were divided into three groups. Group 1 was the treatment group using an active recovery in cold water at 15 oC for 7.5 minutes. Group 2 was the treatment group using a passive recovery in cold water at 15oC for 7.5 minutes. Group 3 was the control group using a passive recovery. The results of this study showed that both recovery methods, the CWI with active recovery and the CWI with passive recovery, positively affected the elimination of lactate in the athlete body. However, the results showed that the CWI with active recovery tended to have a better effect on reducing lactate levels than passive recovery methods. Based on the research results, there were significant influences of both types of recovery, the active recovery and the passive recovery, and a substantial influence of the cold-water immersion in an active recovery on the lactate clearance. The active recovery reduced blood lactic acid levels more efficiently than the passive recovery. Several factors, such as the water temperature, recovery time, and intensity of previous physical activity, might have influenced the results of this study.